The affirmative content in the semantic structure of lexems - Гурко, Олена Василівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 1970)
The lexical meaning of words that transmit statement has been found out. It is singled out those parts of speech, which semantic structure realizes the most clearly affirmative meaning, represented synonymous equivalents to the main lexems that transfer statement. It has been noticed that the verbs and adjectives are one of the most productive means to implement affirmative semantics, and nouns with the help of affirmative content transmit mental affirmative act. Revealed that the intention of statement pass numerals of definite and indefinite number and confirmation is used for correctly interpreting opposing concepts of attribute semantics. Prospects for further scientific studies to identify the specificities use nouns that transfer statements in different scientific styles.